"Good Catch, Kiddo"—Enhancing Patient Safety in the Pediatric Emergency Department Through Simulation. Issue 1 (January 2022) - Shaikh, Ulfat; Natale, JoAnne E.; Till, Dale A.; Julie, Ian M.
Abstract : Objectives: Adverse events that affect patient safety are a significant concern in pediatrics. Increasing situational awareness, identifying errors and near misses, and reporting them using organizational incident reporting systems enables mitigation of harm. Methods: We designed and tested a brief, interactive, and easily replicable simulation activity for medical students, and emergency medicine interns and pediatric interns to strengthen their skills and enhance their self-efficacy in identifying and reporting patient safety hazards. Hazards fell into the categories of situational safety, patient identification and privacy, infection prevention, treatment errors, and issues with electronic health records (EHRs). Results: The simulation training significantly increased the self-efficacy of medical students and interns in identifying and reporting patient safety hazards. Learners were very satisfied with the simulation training, successfully recognized key patient safety hazards, provided feedback to improve the training, and improved their ability to report hazards through organizational incident reporting systems. Patient safety hazards associated with patient misidentification were recognized most frequently, whereas safety hazards associated with EHRs were missed with the greatest frequency. Conclusions: The simulation training enabled learners to identify hazards and near misses and enhanced their ability to report hazards through organizational incident reporting systems. Learners at all levels of training identified safety hazards at comparable rates, which demonstrates the role that trainees play in critically observing clinical settings with fresh eyes and identifying and reporting patient safety hazards. Interventions to promote patient safety need to prioritize building situational awareness of potential hazards associated with EHR use. Abstract : Supplemental digital content is available in the text.